Skin Dosimetric Comparison of 3DCRT and IMRT Planning for Post-Mastectomy Breast Radiotherapy - F. K. Hentihu; A. K. Anto; R. S. Nugroho (Atom Indonesia, 2022)
Breast cancer is the most common cancer for incidence and mortality among females globally and in Indonesia. Mastectomy is still the most common surgery for female breast cancer in Indonesia. After the mastectomy, several patients will receive a whole breast radiotherapy session. About 68.75% of breast cancer patients in the radiotherapy department at Lavalette Hospital during 2019 had undergone the mastectomy. Radiotherapy treatment for breast cancer can be delivered using Intensity Modulated Radiotherapy (IMRT) or 3D-Conformal Radiotherapy (3DCRT) technique. This study is aimed to compare the skin dosimetric between IMRT and 3DCRT for post-mastectomy breast radiotherapy. Left-sided breast cancer patients who underwent radiotherapy at Lavalette Hospital during 2019 were included in this study, and 15 patients were selected. All patients received 50 Gy in 25 fractions over 5 weeks using 6 MV photons. The planning target volume (PTV) and organ at risk (OAR) were delineated. Skin with 3 mm thickness along PTV was also contoured for evaluating the dose delivered to the skin. The treatment planning was conducted using 3DCRT and 5 fields IMRT planning. The plans were optimized for at least 95% of the prescribed dose to cover 95% volume of the PTV. The mean dose and maximum dose were used for evaluating and comparing each plan. The skin’s mean dose from 3DCRT planning was 24.65 ± 4.12 Gy and 22.85 ± 3.68 Gy (p = 0.002) for IMRT planning. Meanwhile, skin maximum doses were 54.15 ± 0.68 Gy and 53.89 ± 1.05 Gy         (p = 0.001) respectively for 3DCRT and IMRT planning. These results showed that IMRT offered a lower dose to the skin and a better skin-sparing effect than 3DCRT.